Outbreak eaudiobook - Bunn, Davis (Recorded Books Inc., 2019)
The waters off the West African coast are a menacing red, full of algae thick enough to stand on in places. In nearby villages, mysterious deaths start to occur—and the panic mounts. But before an alarm can be sounded, the sea currents shift, the algae vanishes, and the deaths stop. Everyone is relieved when things return to normal, and local government officials are happy to sweep the publicity nightmare under a rug.